Abundance, Biomass and Diversity of Soil Fauna at Different Ecosystems in Jakenan, Pati, Central Java - Rahayu Widyastuti (Jurnal Ilmu Tanah dan Lingkungan, 2004)
The assessment of soil fauna in three different ecosystems namely teak forest, home garden and fallow paddy field had been studied in Pati, Central Java. The soil fauna was collected using a soil corer of 20 cm diameter to the depth of 0-15 cm from 5 randomized points in the above ecosystems. The soil fauna was t$en extracted in a Berlese funnel extractor. Soil fauna in the home garden showed the highest abundance (2 940 individual m--), followed by teak forest (2 340 individual m-?) and fallow paddy (1 790 individual m-?). The home garden had also a higher soil fauna diversity (2.06) compared to the teak forest (1.82) and fallow paddy (1.67). In terms of soil fauna biomass, the teak forest had a higher value (961 mg m-3 compared to the home garden (368 mg m-3 and fallow paddy (309 mg m"). In these three ecosystems, two fauna groups, i.e. Collembola and Acari were the most abundant animals. Poor vegetation cover tends to reduce the population of soil fauna in the fallow paddy. field, whereas vegetation, found in the home garden and teak forest protected the soil surface from direct sunshine and maintained soil moisture. This condition presumably provided a more favorable habitat for soil fauna. Thus, vegetation cover appears important to maintain soil moisture and soil living-organisms. Keywords: soil fauna, abundance, diversity, ecosystem, vegetation cover